2016
DOI: 10.1177/0748233716675218
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pH on thein vitropermeation of rhodium through human skin

Abstract: Workers in precious metals refineries are at risk of exposure to salt compounds of the platinum group metals through inhalation, as well as through the skin. Rhodium salt permeation through the skin has previously been proven using rhodium trichloride (RhCl) dissolved in synthetic sweat at a pH of 6.5. However, the skin surface pH of refinery workers may be lower than 6.5. The aim of this study was to investigate the influence of pH 6.5 and 4.5 on the in vitro permeation of rhodium through intact Caucasian ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The main routes for occupational exposure to Pd, Rh, and Ir are via inhalation and, to a lesser extent, the skin. Absorption through inhalation is of particular importance in the refining and automotive catalyst industries. , Similarly to Pt, in vitro permeation studies have also shown that Pd nanoparticles and Rh are permeable through intact human skin, ,, which suggests that the skin as a route of exposure may contribute to the total body burden of PGMs.…”
Section: Routes Of Exposurementioning
confidence: 99%
“…The main routes for occupational exposure to Pd, Rh, and Ir are via inhalation and, to a lesser extent, the skin. Absorption through inhalation is of particular importance in the refining and automotive catalyst industries. , Similarly to Pt, in vitro permeation studies have also shown that Pd nanoparticles and Rh are permeable through intact human skin, ,, which suggests that the skin as a route of exposure may contribute to the total body burden of PGMs.…”
Section: Routes Of Exposurementioning
confidence: 99%
“…pH has been shown to affect the permeation of rhodium and chromium in human ex vivo skin, where a reduction in pH from 6.5 to 4.5 significantly increased penetration. 34,35 In the study using nickel salts, the pattern with a decreasing surface skin dose as a function of exposure time is clearly visible, 14 and likewise, the amount of nickel in SC as a function of the dose applied. The fact that the total recovered dose of nickel (Tapes 1-10) does not amount to more than 35%-48% of the applied dose in our study, might indicate that nickel has penetrated further into SC and the living epidermis.…”
Section: Discussionmentioning
confidence: 94%
“…Another explanation may be difference in pH, which is likely lower in the present study due to exposure with nickel solution in dilute HNO 3 . pH has been shown to affect the permeation of rhodium and chromium in human ex vivo skin, where a reduction in pH from 6.5 to 4.5 significantly increased penetration 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…In vitro diffusion cell experiments showed penetration of rhodium salts and nanoparticles into, but low or no permeation through, an intact human skin. Permeation increased when the skin was damaged or when the pH on the skin was decreased (Franken et al 2014;Mauro et al 2015;Jansen Van Rensburg et al 2017).…”
Section: Rhodiummentioning
confidence: 99%